Effectiveness of Communication Through Zoom Meeting Media On Student Attitiudes - Mujianto, Haryadi; Leadya Raturahmi; Hilman Aliansyah (LPPM Stikosa - AWS, 2023)
The purpose of this study is to find out the role of lecturers and students in conducting distance learning (PJJ) through zoom meeting with the level of communication effectiveness on student attitudes. The research method used is a questionnaire survey method to calculate the Validity and Reliability test. The approach used in this study is a quantitative approach with data collection techniques, namely questionnaires. The subjects of this research are active students of the Faculty of Communication and Information, University of Garut as many as 700 people. The sampling technique used is simple random sampling. The results showed that there was an effect of the effectiveness of communication through the media zoom meeting on the attitude of the students of Fkominfo Garut University, this can be seen from the total score obtained by 5083, where the results are between the 3930 line and the 5280 line. The attitude of students of the Garut University communication science study program during learning through the media zoom is in the good category. Because the score shows the number 6632, where the result is between the 5016 line and the 6688 line.